Evidence of active demyelination during early stage of HIV-1 lnfection - Guterrez, Alex Taranto; Silva, Andrea Alice; Quirico-Santos, Thereza (Brazilian Journal of Sexually Transmitted Diseases, 1996)
The central nervous system is considered an early target for the human immunodeticiency virus type 1 (HIV-1). Serum and cerebrospinal fluid (CSF) from 20 HIV positive patients, including 14 with AIDS-dementia complex (CDC stage IV) and 6 asymptomatic individuais (CDC stage ll) were analysed by enzyme immunoassay for detection of antibodies to na tive myelin basic protein (MBP) and for the aminoacid sequcncc 68-84 exposed after partia! degradation of native MBP. Control groups included HIV -1 negative patients with degenera tive and for vascular dementia, chro1úc multiplesclerosis (MS) and individuais without any sign of neurological or cognitive disturbances. Serum and CSF samples from MS and HIV-1 infectcd paticnts showed severa! oligoclonal bands running in the gamma region. AIDS-dementia complex (ADC) patients and HIV-1 infected asymptomatic individuais had increasingly high intrathecal lgG specific antibody titres for the aminoacid sequence 68-84 of MBP. Such alteration consistently paralleled development of neurological disturbances and appearance of CNS demyelinating plaques. Preforential immune recognition of this myelin epitope within the CSF during early stages of HIV -1 infcction might point for an ongoing process of aclive demyelination and ultimately indicate subclinical CNS involvement.